(untitled) (De Rebus Antiquis, 2020)
This paper it is discussed the public games held in Rome during the monarchy. Its creation is due to religious causes, related to fertility (Consualia, ludi Taurei) or to war (Equirria, equus October). The religious and politic fulfillment of the games materializes in the ludi Romani, introduced by King Tarquinius Priscus. It is also considered the so called lusus Troiae, equestrian game exclusive for young people, and likewise with an archaic origin.